Recognizing Biogeomorphology: Analysis of Academic-Scientific Production and Distribution of Studies by Geomorphological Environments - Valdati, Jairo; Rocha Souza, Pedro Cauê (Revista Brasileira de Geomorfologia, 2025)
Biogeomorphology focuses on the study of interactions between biotic and abiotic factors in geomorphological processes and systems, dealing with the dynamics between living organisms and their physical environments. It is an area of study between Geomorphology and Ecology, aiming to understand the influences between landforms and the distribution and development of organisms, and vice versa. In the present article the authors made a bibliometric analysis of scientific and academic production in biogeomorphology, using the Scopus database as the research source. The bibliometric research and analysis were carried out in two stages: in the first, the goal was to depict the state of art biogeomorphological research; while in the second phase, biogeomorphological works were inventoried according to the different geomorphological environments they focus on: i) coastal environments; ii) fluvial environments; and iii) slope environments. For better characterization, the research considered only works published until December 2024. As results, this work presents the historical evolution of Biogeomorphology as a discipline, both in general and through its subfields, identifying its main authors and works, research-leading countries, key bibliographic sources, and an analysis of the co-occurrence of keywords.